Development of an Electrochemical Methodology for the Quantification of β-estradiol in Pharmaceutical Formulation - Thais Silva Alves; Antonio Rogério Fiorucci; Gilberto José Arruda (Orbital: The Electronic Journal of Chemistry, 2019)
This paper describes a simple, inexpensive, highly sensitive, and efficient electrochemical method to determine Estradiol in pharmaceutical formulations. The oxidation reaction on the electrode surface was electrochemically characterized by cyclic voltammetry (CV) and square wave voltammetry (SWV). The investigation of Estradiol at carbon paste electrode revealed a non-reversible oxidation peak at +640 mV vs. Ag/AgCl, which was used for electrochemical detection of Estradiol. The operating parameters (pH, frequency, step potential, and amplitude) were optimized in relation to the peak current intensity, and a calibration curve was set up in a concentration range of 0.059 - 2.997 mg L-1, with a detection limit of 21.85 µg L-1. After calibration curve was plotted, the developed procedure was applied to determine Estradiol in parmacheutical formulation. These results show that the proposed method can be used for Estradiol quantification in pharmaceutical formulations with high sensitivity, specificity, stability, and reproducibility, and can be applied in analytical routines in laboratories of quality control analysis in drugs.DOI: http://dx.doi.org/10.17807/orbital.v11i4.1332